An exploration into registered nurses' knowledge of adult fever in Scotland: A mixed method study. (August 2022) - Chen, Lu-Yen A.; Fawcett, Tonks N.; Chandler, Colin
Abstract: Background: Fever may be a result of many causes, infective or non-infective. Nurses' fever management can be affected by their knowledge and beliefs and also by patients' beliefs. Consequently, an understanding of fever is vital in the diagnosis, treatment and follow-up of various ailments and diseases. Greater knowledge of fever will guide more accurate assessments of the epidemiology of fever and its management. Objectives: This study explored nurses' knowledge in the context of fever and identified factors that affected this knowledge acquisition. Methods: A mixed methods approach was used with a validated questionnaire designed to gather information about nurses' knowledge of fever. This was followed up by semi-structured interviews to explore factors associated with the acquisition of fever knowledge. The online survey was distributed to registered nurses in Scotland. Results: A total of 177 questionnaires were completed. The questionnaires were scored with a correct answer 1 point, while a wrong answer −1 point. The mean total score in the knowledge section was 0.47. Only 49.2 % of participants scored above 0. The stepwise linear regression demonstrated working experience in critical care unit, acute care unit and the role of nurse practitioner together could predict 10 % of the total knowledge score (P < 0.05). Through analysis of associations and qualitative data, it was found that many factors had contributed to the nurses' knowledge about fever, specifically educational content, individual confidence and the Sepsis Six bundle. Conclusions: Considerable misconceptions were found to exist in the nurses' understanding of fever. Only a few factors were found to be associated with the total knowledge score. It was highlighted that the due to the strong influence of the Sepsis Six bundle, participants often assumed a direct causal connection between fever and infectious disease or sepsis. The study result indicated a concern in nurses' acquisition of fever knowledge. Tweetable abstract: Misconceptions from foundational learning were found in nurses' understanding of fever. However, the Sepsis 6 was found to impact their current knowledge of fever.